631 The Time to Therapeutic Serum Levels of Vancomycin in Orthopaedic Patients. (4th May 2021) - Rankin, C; Robinson, P; McCann, C; Cockburn, A; Palenzuela, E
Abstract: Introduction: Vancomycin is a commonly used antibiotic in the treatment of deep-seated infections. However, the current dosing calculator utilized in NHS Lothian may not adequately achieve therapeutic vancomycin serum concentrations (VSC), of 15-20mg/L, in a timely manner. We aimed to reaudit the length of time for vancomycin to reach therapeutic levels in orthopaedic patients using the new Lothian calculator. A previous audit loop looked at the current calculator in 2018. Method: Inclusion criteria orthopaedic patients who were treated with vancomycin at the Royal Infirmary Edinburgh, data collection to finish mid-September. The duration to reach the therapeutic SVC, initial trough SVC and serial levels were recorded. A life-table analysis will be used to examine the data. Results: First audit had Twenty-three patients. The mean initial trough VSC was 12.7mg/L. The mean duration to therapeutic VSC was 5.2 (± 1.3) days. Statistics not completed for second cycle, but initial data shows improvement in time to VSC. Conclusions: A delay in reaching therapeutic concentrations was observed in a significant proportion of patients using the current calculator. A more rapid achievement of therapeutic levels is required to maximize the period of antibiotic delivery and subsequently improve patient outcomes. The new calculator pilot will hopefully show that improvement.